Multilayer structure, formed body, and method for producing formed body

By directly stacking the gas barrier layer and the polyurethane layer in the multilayer structure and controlling the number of layers, the problem of layer peeling when the multilayer structure is exposed in the organic solvent is solved, and high gas barrier properties and bending resistance are achieved.

CN114390974BActive Publication Date: 2025-03-18KURARAY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202080067019.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-24
Filing Date
2020-09-24
Publication Date
2025-03-18
Estimated Expiration
2040-09-24

AI Technical Summary

Technical Problem

The existing multilayer structure is prone to interlayer peeling when exposed to organic solvents, resulting in a decrease in gas barrier properties and bending resistance.

Method used

A multi-layer structure consisting of a gas barrier layer (A) and a polyurethane layer (B) is adopted, wherein the gas barrier layer includes an ethylene-vinyl alcohol copolymer and a thermoplastic resin having a reactive functional group. The polyurethane layer includes a thermoplastic polyurethane. Both are formed by direct lamination to ensure that the number of layers is 9 or more and 300 or less.

Benefits of technology

It is achieved that high gas barrier properties and bending resistance can be maintained when exposed to organic solvents, and interlayer adhesion and solvent resistance can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114390974B_ABST
    Figure CN114390974B_ABST
Patent Text Reader

Abstract

Provided are a multilayer structure having excellent solvent resistance while maintaining gas barrier properties and bending resistance, a molded article having such a multilayer structure, and a method for producing the molded article. A multilayer structure having a gas barrier layer (A) and a polyurethane layer (B), wherein the gas barrier layer (A) comprises an ethylene-vinyl alcohol copolymer (a1) and a thermoplastic resin (a2) having a functional group that can react with the ethylene-vinyl alcohol copolymer (a1), and the polyurethane layer (B) comprises a thermoplastic polyurethane (b), wherein the content of the thermoplastic resin (a2) is 0.1 to 30 parts by mass relative to 100 parts by mass of the total of the ethylene-vinyl alcohol copolymer (a1) and the thermoplastic resin (a2), and wherein the multilayer structure comprises a structure in which at least one set of gas barrier layers (A) and polyurethane layers (B) are directly laminated, and the total number of gas barrier layers (A) and polyurethane layers (B) is 9 or more and 300 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multilayer structure, a formed body and a method for producing the formed body. Background Art

[0002] Films obtained using resins having gas barrier properties such as ethylene-vinyl alcohol copolymers are widely used for various purposes such as food and medical packaging materials. Recently, various multilayer structures having a plurality of resin layers having a single layer thickness of the micrometer order or submicrometer order have been proposed for the purpose of improving various properties such as gas barrier properties.

[0003] As a conventional multilayer structure having a plurality of ethylene-vinyl alcohol copolymer resin layers stacked thereon, for example, Patent Document 1 describes a multilayer structure having a total of 8 or more layers, the layers being a layer formed of a resin composition containing a gas barrier resin such as an ethylene-vinyl alcohol copolymer and a layer formed of a thermoplastic resin such as a thermoplastic polyurethane. Patent Document 1 describes that by making any of the adjacent resin layers contain a metal salt, a multilayer structure having excellent interlayer adhesion, bending resistance, etc. can be provided.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: International Publication No. 2011 / 068105. Summary of the invention

[0007] Problems to be solved by the invention

[0008] The multilayer structure as described above is sometimes used for exposure to organic solvents such as methanol. In addition, when the multilayer structure is colored, there is also a case where the multilayer structure is immersed in an organic solvent containing a colorant for coloring. However, if the multilayer structure with more than 8 layers described in Patent Document 1 is exposed to an organic solvent, interlayer peeling sometimes occurs locally. Therefore, it is sought to maintain the physical properties such as gas barrier properties and bending resistance achieved by the multilayer structure with more than 8 layers, and the multilayer structure is also excellent in resistance to interlayer peeling when exposed to an organic solvent. It should be noted that interlayer peeling when exposed to an organic solvent is a subject that is only significantly observed in multilayer structures with a large total number of layers.

[0009] The present invention has been made based on the above circumstances, and an object of the present invention is to provide a multilayer structure having excellent solvent resistance while maintaining gas barrier properties and bending resistance, a molded article having such a multilayer structure, and a method for producing the molded article.

[0010] Solutions for solving problems

[0011] According to the present invention, the above object is achieved by providing the following technical solutions.

[0012] [1] A multilayer structure comprising a gas barrier layer (A) and a polyurethane layer (B), wherein the gas barrier layer (A) comprises an ethylene-vinyl alcohol copolymer (a1) and a thermoplastic resin (a2) having a functional group capable of reacting with the ethylene-vinyl alcohol copolymer (a1), and the polyurethane layer (B) comprises a thermoplastic polyurethane (b), wherein the content of the thermoplastic resin (a2) is 0.1 to 30 parts by mass based on 100 parts by mass of the total of the ethylene-vinyl alcohol copolymer (a1) and the thermoplastic resin (a2), and wherein the multilayer structure comprises a structure in which at least one set of the gas barrier layer (A) and the polyurethane layer (B) are directly laminated, and the total number of layers of the gas barrier layer (A) and the number of layers of the polyurethane layer (B) is 9 or more and 300 or less;

[0013] [2] The multilayer structure according to [1], wherein the functional group possessed by the thermoplastic resin (a2) is a carboxyl group or a derivative thereof;

[0014] [3] The multilayer structure according to [1] or [2], wherein the acid value of the thermoplastic resin (a2) is 0.5 to 50 mgKOH / g;

[0015] [4] The multilayer structure according to any one of [1] to [3], wherein the thermoplastic resin (a2) is at least one selected from the group consisting of modified polyethylene, modified polypropylene, modified ethylene-vinyl acetate copolymer and modified ethylene-ethyl acrylate copolymer;

[0016] [5] The multilayer structure according to any one of [1] to [4], wherein the ethylene unit content of the ethylene-vinyl alcohol copolymer (a1) is 20 mol% or more and 60 mol% or less;

[0017] [6] The multilayer structure according to any one of [1] to [5], wherein the gas barrier layer (A) further comprises a higher fatty acid metal salt (a3);

[0018] [7] The multilayer structure according to any one of [1] to [6], wherein the gas barrier layer (A) and the polyurethane layer (B) are alternately laminated;

[0019] [8] The multilayer structure according to [7], wherein the polyurethane layer (B) comprises a polyurethane layer (B1) and a polyurethane layer (B2), wherein the polyurethane layer (B1) is directly laminated with the gas barrier layer (A) on both sides, and the polyurethane layer (B2) is directly laminated with the gas barrier layer (A) only on one side.

[0020] [9] The multilayer structure according to [8], comprising a protective layer (D) directly laminated on the polyurethane layer (B2), wherein the protective layer (D) comprises a thermoplastic polyurethane (x).

[0021]

[10] The multilayer structure according to [9], wherein the protective layer (D) contains an ethylene-vinyl alcohol copolymer (y).

[0022]

[11] The multilayer structure according to [9] or

[10] , wherein the average thickness of each protective layer (D) is 300 μm or more and 800 μm or less.

[0023]

[12] The multilayer structure according to any one of [1] to

[11] , wherein the outermost layer is a polyurethane layer (B);

[0024]

[13] The multilayer structure according to any one of [1] to

[12] , wherein the average thickness of each gas barrier layer (A) is 0.1 μm or more and 15 μm or less;

[0025]

[14] The multilayer structure according to any one of [1] to

[13] , wherein the average thickness of each polyurethane layer (B) is 0.1 μm or more and 30 μm or less;

[0026]

[15] A multilayer structure according to any one of [1] to

[14] , wherein the gas barrier layer (A) forms a phase separation structure having a sea phase and an island phase, the sea phase comprises an ethylene-vinyl alcohol copolymer (a1), and the island phase comprises a thermoplastic resin (a2).

[0027]

[16] The multilayer structure according to

[15] , further comprising a phase containing the ethylene-vinyl alcohol copolymer (a1) inside the island phase.

[0028]

[17] A molded article comprising the multilayer structure according to any one of [1] to

[16] , wherein at least one of the gas barrier layer (A) and the polyurethane layer (B) contains a colorant;

[0029]

[18] A method for producing a molded article, comprising the step of contacting the multilayer structure according to any one of [1] to

[16] with a treatment liquid containing an organic solvent;

[0030]

[19] The method for producing a molded body according to

[18] , wherein the treatment liquid contains a colorant.

[0031] Effects of the Invention

[0032] According to the present invention, a multilayer structure having excellent solvent resistance while maintaining gas barrier properties and flex resistance, and a product including the multilayer structure can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a TEM image of a cross section of the A layer in the multilayer structure of Example 1. DETAILED DESCRIPTION

[0034] 〈Multilayer structure〉

[0035] The multilayer structure of the present invention comprises a gas barrier layer (A) (hereinafter sometimes abbreviated as “A layer”) and a polyurethane layer (B) (hereinafter sometimes abbreviated as “B layer”), wherein the gas barrier layer (A) comprises an ethylene-vinyl alcohol copolymer (a1) (hereinafter sometimes abbreviated as “EVOH (a1)”) and a thermoplastic resin (a2) having a functional group that can react with EVOH (a1), and the polyurethane layer (B) comprises a thermoplastic polyurethane (b) (hereinafter sometimes abbreviated as “TPU (b)”), wherein the content of the thermoplastic resin (a2) is 0.1 to 30 parts by mass relative to 100 parts by mass of the total of the ethylene-vinyl alcohol copolymer (a1) and the thermoplastic resin (a2), and the multilayer structure comprises a structure in which at least one set of the gas barrier layer (A) and the polyurethane layer (B) are directly laminated, and the total number of layers of the gas barrier layer (A) and the number of layers of the polyurethane layer (B) is 9 or more and 300 or less. According to the present invention, by including a structure in which at least one set of A layer and B layer are directly laminated, the total number of A layer and B layer is 9 or more layers, and A layer contains a specific amount of thermoplastic resin (a2), it is possible to provide a multilayer structure that maintains high gas barrier properties and bending resistance obtained by the multilayer structure, and has excellent solvent resistance and excellent resistance to interlayer delamination even when exposed to organic solvents. It should be noted that in the present specification, "gas barrier properties" can be evaluated based on the measured value of oxygen permeability, and specifically, can be evaluated using the method described in the Examples.

[0036] The multilayer structure of the present invention may be composed of only layer A and layer B, or may have other resin layers other than layer A and layer B. The multilayer structure of the present invention may further have layers other than the resin layer. From the viewpoint of maintaining gas barrier properties after bending, it is preferably composed of only layer A and layer B. When other resin layers are provided, the other resin layers are preferably the outermost layers.

[0037] The multilayer structure of the present invention comprises a structure in which at least one group of A layers and B layers are directly stacked, preferably a structure in which at least four groups of A layers and B layers are directly stacked, and preferably all A layers and B layers constituting the multilayer structure are directly stacked with any A layer or B layer. By having the above-mentioned directly stacked structure, the effect of maintaining the gas barrier properties after bending can be achieved. In addition, from the viewpoint of maintaining the gas barrier properties after bending, it is preferred that the A layers and B layers are alternately stacked.

[0038] The multilayer structure of the present invention preferably has a symmetrical structure (e.g., B layer / A layer / B layer / A layer / B layer / A layer / B layer / A layer / B layer / A layer / B layer) from the viewpoint of enabling efficient coextrusion.

[0039] In the case where the A layer and the B layer are alternately laminated, from the viewpoint of further suppressing the reduction in gas barrier properties when the layer is bent, the B layer preferably includes a polyurethane layer (B1) (hereinafter sometimes abbreviated as "B1 layer") and a polyurethane layer (B2) (hereinafter sometimes abbreviated as "B2 layer"), wherein the polyurethane layer (B1) is directly laminated with the A layer on both sides, and the polyurethane layer (B2) is directly laminated with the A layer only on one side. That is, it is preferred that at least one outermost layer in the alternately laminated portion of the A layer and the B layer is the B layer. It is more preferred that the B layer as at least one outermost layer in the alternately laminated portion is the B2 layer, and the other B layer is the B1 layer. Furthermore, the B layer more preferably includes two B2 layers. That is, it is more preferred that the two outermost layers in the alternately laminated portion of the A layer and the B layer are the B layer.

[0040] In the case of having a B2 layer, from the viewpoint of further suppressing the reduction in gas barrier properties when it is bent, the multilayer structure of the present invention preferably has a protective layer (D) (hereinafter sometimes abbreviated as "D layer") directly laminated on the B2 layer. The protective layer (D) is a layer containing a thermoplastic polyurethane (x) (hereinafter sometimes abbreviated as "TPU (x)"), preferably containing an ethylene-vinyl alcohol copolymer (y) (hereinafter sometimes abbreviated as "EVOH (y)"). As a layer structure of a multilayer structure having a D layer, D layer / B2 layer / A layer / B1 layer / A layer / B1 layer / A layer / B1 layer / A layer / B2 layer / D layer can be exemplified. The D layer is preferably the outermost layer. The D layer can be arranged only on one side, preferably on both sides. The multilayer structure of the present invention can be a structure consisting only of an A layer and a B layer, a structure consisting only of an A layer, a B layer and a D layer, or a structure further having other resin layers.

[0041] The number of layers of the A layer constituting the multilayer structure of the present invention is preferably 4 or more layers, more preferably 6 or more layers, and further preferably 8 or more layers. If the number of layers of the A layer is 4 or more layers, the gas barrier properties after bending can be further maintained, which is preferred. On the other hand, the number of layers of the A layer may be 150 or less layers.

[0042] The number of layers of the B layer constituting the multilayer structure of the present invention is preferably 4 or more layers, more preferably 6 or more layers, and further preferably 8 or more layers. If the number of layers of the B layer is 4 or more layers, the gas barrier properties after bending can be further maintained, which is preferred. On the other hand, the number of layers of the B layer may be 150 or less layers.

[0043] The total number of layers of the A layer and the number of layers of the B layer constituting the multilayer structure of the present invention is 9 layers or more, preferably 11 layers or more, more preferably 15 layers or more, further preferably 25 layers or more, and particularly preferably 30 layers or more. On the other hand, the total number of layers of the A layer and the number of layers of the B layer is 300 layers or less, preferably 200 layers or less, and more preferably 100 layers or less. The total number of layers of the multilayer structure is also preferably within the above range. By making the multilayer structure into a multilayer structure in this way, even if defects such as pinholes and cracks are generated in a certain A layer due to bending, the gas barrier properties can be maintained by using other A layers, and as a result, the gas barrier properties, durability and other characteristics of the multilayer structure as a whole can be provided.

[0044] In addition, the problem of interlayer peeling when exposed to an organic solvent, which is related to solvent resistance, is a unique problem that occurs significantly in the case of a conventional multilayer structure with a large number of layers. This is considered to be because: when the number of layers is large, the influence of the swelling of each layer by the solvent becomes greater. In a multilayer structure having a total of 9 layers or more of A layers and B layers, by making the A layer contain a predetermined amount of thermoplastic resin (a2) and the like, it is possible to enjoy the advantage of excellent solvent resistance despite being such a multilayer structure.

[0045] The average thickness of one A layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and further preferably 0.3 μm or more. On the other hand, the average thickness of one A layer is preferably 15 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, and particularly preferably 2 μm or less. If the average thickness of one A layer is 0.1 μm or more, the following tendency is shown: it is easier to form with uniform thickness, and gas barrier properties, durability, solvent resistance, etc. are further improved. On the contrary, if the average thickness of one A layer is 15 μm or less, softness, etc. are improved, and as a result, there is also the following tendency: durability, etc. are also improved, and interlayer delamination is not easy to occur when exposed to organic solvents.

[0046] The average thickness of one B layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, further preferably 1 μm or more, and particularly preferably 3 μm or more. On the other hand, the average thickness of one B layer is preferably 30 μm or less, more preferably 15 μm or less, further preferably 10 μm or less, and particularly preferably 8 μm or less. If the average thickness of one B layer is 0.1 μm or more, the following tendency is shown: it is easier to form with uniform thickness, and durability, solvent resistance, etc. are further improved. In addition, it is easy to show sufficient softness. On the contrary, if the average thickness of one B layer is 30 μm or less, there is also the following tendency: interlayer adhesion and gas barrier properties are improved, and interlayer peeling is not easy to occur when exposed to organic solvents.

[0047] The average thickness of each layer of the B1 layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, further preferably 1 μm or more, and particularly preferably 3 μm or more. On the other hand, the average thickness of each layer of the B1 layer is preferably 20 μm or less, more preferably 15 μm or less, further preferably 10 μm or less, and particularly preferably 8 μm or less. If the average thickness of each layer of the B1 layer is 0.1 μm or more, the following tendency is presented: it is relatively easy to form with uniform thickness, and the durability is further improved. In addition, it is easy to show sufficient softness. On the contrary, if the average thickness of each layer of the B1 layer is 20 μm or less, there is a tendency to improve interlayer adhesion and gas barrier properties. In addition, when the average thickness of each layer of the B1 layer is 20 μm or less, there is a tendency to further improve recyclability. It can be inferred that when melt-kneading is performed in order to reuse scraps, the metal salt contained in the A layer as needed can be effectively transferred to the polyurethane of the B1 layer as a whole. The term "recyclability" refers to a property that allows easy recycling, such as small fluctuations in the rotation torque of the extruder screw when melt-molding is performed again to reuse scraps of the multilayer structure.

[0048] The average thickness of each layer of the B2 layer is preferably more than 1 μm, more preferably more than 3 μm. On the other hand, the average thickness of each layer of the B2 layer is preferably less than 30 μm, more preferably less than 25 μm, and more preferably less than 20 μm. If the average thickness of each layer of the B2 layer is more than 1 μm, the durability tends to be further improved. In addition, it is easy to show sufficient flexibility. On the contrary, if the average thickness of each layer of the B2 layer is less than 30 μm, the interlayer adhesion and gas barrier properties tend to be improved. In addition, when the average thickness of each layer of the B2 layer is less than 30 μm, there is a tendency to further improve reusability. It can be inferred that when melt-kneading is performed in order to reuse scraps, the metal salt contained in the A layer as needed can be effectively transferred to the polyurethane of the B layer as a whole.

[0049] When the multilayer structure of the present invention includes a D layer, the average thickness of each layer of the D layer is preferably 300 μm or more, more preferably 350 μm or more, and further preferably 400 μm or more. On the other hand, the average thickness of the D layer is preferably 800 μm or less, more preferably 750 μm or less, and further preferably 700 μm or less. If the average thickness of the D layer is 300 μm or more, the durability tends to be further improved. In addition, it is easy to show sufficient flexibility. On the contrary, if the average thickness of the D layer is 800 μm or less, the gas barrier properties after bending tend to be improved.

[0050] The total thickness of all layers of layer A and all layers of layer B can be, for example, 5 μm or more, preferably 10 μm or more, more preferably 15 μm or more, and further preferably 30 μm or more. On the other hand, the total thickness of all layers of layer A and all layers of layer B is preferably 500 μm or less, more preferably 300 μm or less, and further preferably 100 μm or less. When the total thickness of all layers of layer A and all layers of layer B is 10 μm or more, there is a tendency to further improve bending resistance, durability, gas barrier properties, solvent resistance, etc. On the contrary, when the total thickness is 500 μm or less, flexibility, formability, etc. are improved, and it is possible to achieve improved bending resistance and suppression of manufacturing costs. In addition, by making the amount of resin in layer B moderate, etc., recyclability is sometimes also improved. Here, the total thickness of all layers refers to the sum of the average thickness of each layer. In a multilayer structure in which only layer A and layer B are present, the thickness of the entire multilayer structure in which only layer A and layer B are present can be set to the total thickness. The average thickness of each layer is set to the average value of the cross-sectional thickness at any 10 points.

[0051] The ratio of the average thickness of each layer of the A layer to the average thickness of each layer of the B layer (A layer / B layer) can be, for example, 0.05 or more, preferably 0.1 or more, more preferably 0.15 or more, and further preferably 0.2 or 0.25 or more. In addition, the above ratio is preferably less than 1, preferably less than 0.8, and more preferably less than 0.6. If the ratio (A / B) of the average thickness of each layer of the A layer to the average thickness of each layer of the B layer is more than 0.1, the cracks of the A layer caused by the stress during bending are reduced, and therefore, the reduction of gas barrier properties is suppressed, and in addition, solvent resistance is also improved. If the ratio (A / B) is less than 1, the stress during bending is relieved by the B layer, and therefore, the cracks of the A layer are reduced, the reduction of gas barrier properties is suppressed, and the solvent resistance is also improved. In addition, when the ratio of the average thickness of each layer of the A layer to the average thickness of each layer of the B layer is in the above range, the resin ratio of the A layer to the B layer presents a suitable state for the multilayer structure as a whole, and there is a tendency to improve reusability, etc.

[0052] The overall average thickness of the multilayer structure of the present invention is not particularly limited and can be appropriately set according to the purpose, function, etc. For example, by setting it to a thinner thickness, it is possible to achieve lightweight, and by setting it to a thicker thickness, it is possible to further improve the gas barrier properties, etc. The lower limit of the overall average thickness of the multilayer structure of the present invention can be, for example, 5 μm, 10 μm, 15 μm, 30 μm, 100 μm or 300 μm. On the other hand, the upper limit can be 3 mm, 1 mm, 500 μm, 300 μm or 100 μm.

[0053] The interlayer adhesion between layer A and layer B of the multilayer structure of the present invention is preferably 300g / 15mm or more, more preferably 400g / 15mm or more, and further preferably 500g / 15mm or more. In addition, the interlayer adhesion of the multilayer structure of the present invention can be 1500g / 15mm or less. If the interlayer adhesion is 300g / 15mm or more, there is a tendency that interlayer peeling during bending, etc. is suppressed. As means for improving the interlayer adhesion of the multilayer structure of the present invention, methods such as adjusting the addition amount and acid value of the thermoplastic resin (a2); directly stacking layer A and layer B; and alternately stacking layer A and layer B can be listed. The interlayer adhesion of the multilayer structure of the present invention can be measured using the method described in the examples.

[0054] The multilayer structure of the present invention preferably has an oxygen permeability (OTR) of 20 mL / (m 2 ・day・atm) or less, more preferably 15mL / (m 2 ・day・atm) or less, more preferably 10mL / (m 2 ・day・atm) or less. In addition, OTR can be 0.2mL / (m 2 ・day・atm) or more. If the oxygen permeability of the multilayer structure of the present invention is within the above range, it can be suitably used as a material requiring gas barrier properties, durability, etc. In addition, the OTR of the multilayer structure of the present invention after bending described in the examples is preferably 60 mL / (m 2 ・day・atm) or less, more preferably 20mL / (m 2 ・day・atm) or less. In addition, the OTR after bending can be 0.3mL / (m 2 ・day・atm) or more. If the OTR after bending of the multilayer structure of the present invention is within the above range, it can be suitably used as a material requiring stretchability. The OTR of the present invention and the OTR after bending can be measured by the method described in the Examples.

[0055] 〈A layer〉

[0056] Layer A is a layer comprising EVOH (a1) and a thermoplastic resin (a2) having a functional group capable of reacting with EVOH (a1). In layer A, the content of the thermoplastic resin (a2) is 0.1 to 30 parts by mass relative to a total of 100 parts by mass of EVOH (a1) and the thermoplastic resin (a2). By making layer A contain a specific amount of EVOH (a1) and a thermoplastic resin (a2), a multilayer structure having excellent gas barrier properties and solvent resistance can be obtained. The reason why the multilayer structure of the present invention has excellent solvent resistance is still uncertain, but it can be inferred that, for example, by the presence of a specified amount of thermoplastic resin (a2) having a functional group capable of reacting with EVOH (a1), the swelling of layer A when exposed to a solvent is suppressed, and the high adhesion between layer A and layer B can be maintained.

[0057] The total content of EVOH (a1) and thermoplastic resin (a2) in layer A is sometimes preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, further preferably 99% by mass or more, and may be 100% by mass. In addition, the total content of EVOH (a1) and thermoplastic resin (a2) in all resin components in layer A is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, further preferably 99% by mass or more, and may be 100% by mass.

[0058] The swelling degree of layer A when immersed for 30 minutes at 40°C and 1-propanol / water = 60 / 40 (mass ratio) is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less. In addition, the swelling degree of layer A can be 10% by mass or more. By making the swelling degree of layer A within the above range, the following tendency is presented: it will be close to the swelling degree of layer B, and even in the case of exposure to organic solvents such as immersion in organic solvents, the interlayer peeling of the multilayer structure can be suppressed. As a means of adjusting the swelling degree of layer A to be lower, means such as increasing the amount of thermoplastic resin (a2) added or strengthening the mixing with EVOH (a1) can be listed. It should be noted that the swelling degree of layer A can be measured using the method described in the embodiment.

[0059] 〈EVOH(a1)〉

[0060] EVOH (a1) is a polymer having ethylene units and vinyl alcohol units as main structural units. It should be noted that EVOH (a1) may contain one or more other structural units in addition to ethylene units and vinyl alcohol units. EVOH (a1) is generally obtained by polymerizing ethylene and vinyl ester and saponifying the resulting ethylene-vinyl ester copolymer.

[0061] The ethylene unit content of EVOH (a1) (i.e., the ratio of the number of ethylene units in EVOH (a1) to the total number of monomer units) is preferably 20 mol% or more, more preferably 25 mol% or more, and further preferably 30 mol% or more. On the other hand, the ethylene unit content of EVOH (a1) is preferably 60 mol% or less, more preferably 55 mol% or less. If the ethylene unit content of EVOH (a1) is 20 mol% or more, the gas barrier properties, melt formability, solvent resistance, etc. of the obtained multilayer structure under high humidity are further improved. Conversely, if the ethylene unit content of EVOH (a1) is 60 mol% or less, the gas barrier properties of the obtained multilayer structure are further improved.

[0062] The saponification degree of EVOH (a1) (i.e., the ratio of the number of vinyl alcohol units in EVOH (a1) to the total number of vinyl alcohol units and vinyl ester units) is preferably 80 mol% or more, more preferably 95 mol% or more, and particularly preferably 99 mol% or more. On the other hand, the saponification degree of EVOH (a1) is preferably 99.99 mol% or less. If the saponification degree of EVOH (a1) is 80 mol% or more, there is a tendency for the melt formability to be improved, and sometimes the gas barrier properties of the obtained multilayer structure are further improved, and the coloring resistance and moisture resistance are also improved. On the contrary, when the saponification degree of EVOH (a1) is 99.99 mol% or less, the increase in the manufacturing cost of EVOH (a1) can be suppressed, and the gas barrier properties can be exerted. The EVOH (a1) can also be used alone, and an embodiment in which EVOH having a saponification degree exceeding 99 mol% is blended with other EVOH is also suitable.

[0063] EVOH (a1) preferably has at least one of a structural unit (I) represented by the following formula (I), a structural unit (II) represented by the following formula (II), and a structural unit (III) represented by the following formula (III). By making EVOH (a1) have such structural units, the bending resistance of the obtained multilayer structure can be further improved.

[0064] [Chemistry 1]

[0065]

[0066] In the above formula (I), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. 1 , R 2 and R 3In addition, a part or all of the hydrogen atoms in the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with a hydroxyl group, a carboxyl group, or a halogen atom.

[0067] In the above formula (II), R 4 , R 5 , R 6 and R 7 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. 4 With R 5 or R 6 With R 7 In addition, some or all of the hydrogen atoms in the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with a hydroxyl group, an alkoxy group, a carboxyl group, or a halogen atom.

[0068] In the above formula (III), R 8 , R 9 , R 10 and R 11 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. In addition, a part or all of the hydrogen atoms in the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with a hydroxyl group, an alkoxy group, a carboxyl group, or a halogen atom. 12 and R 13 Each independently represents a hydrogen atom, a formyl group or an alkanoyl group having 2 to 10 carbon atoms.

[0069] The content of the structural units (I), (II) or (III) relative to the total structural units is preferably 0.5 mol% or more, more preferably 1 mol% or more, and further preferably 1.5 mol% or more. On the other hand, the content of the structural units (I), (II) or (III) is preferably 30 mol% or less, more preferably 15 mol% or less, and further preferably 10 mol% or less. By making EVOH (a1) have the structural units shown in (I), (II) or (III) in the above-mentioned range, the flexibility and processing characteristics of the material forming the A layer are improved, and as a result, the stretchability and thermoformability of the obtained multilayer structure can be improved.

[0070] In the above structural units (I), (II) or (III), examples of the above aliphatic hydrocarbon group having 1 to 10 carbon atoms include alkyl and alkenyl groups, examples of the above alicyclic hydrocarbon group having 3 to 10 carbon atoms include cycloalkyl and cycloalkenyl groups, and examples of the above aromatic hydrocarbon group having 6 to 10 carbon atoms include phenyl groups.

[0071] In the above structural unit (I), the above R 1 , R 2 and R 3 Each of them is independently preferably a hydrogen atom, a methyl group, an ethyl group, a hydroxyl group, a hydroxymethyl group, and a hydroxyethyl group, and among these, each of them is independently more preferably a hydrogen atom, a methyl group, a hydroxyl group, and a hydroxymethyl group. 1 , R 2 and R 3 , thereby further improving the stretchability and thermoformability of the obtained multilayer structure.

[0072] The method for making EVOH (a1) contain the above-mentioned structural unit (I) is not particularly limited, and examples thereof include a method of copolymerizing a monomer derived from the structural unit (I) in the polymerization of the above-mentioned ethylene and vinyl ester. Examples of the monomer derived from the structural unit (I) include olefins such as propylene, butene, pentene, and hexene; 3-hydroxy-1-propylene, 3-acyloxy-1-propylene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-hydroxy-1-butene, 4-acyloxy-3-hydroxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-hydroxy-1-pentene, 5-hydroxy Olefins having a hydroxyl group or an ester group such as 4-hydroxy-1-pentene, 4,5-dihydroxy-1-pentene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-hydroxy-3-methyl-1-pentene, 5-hydroxy-3-methyl-1-pentene, 4,5-dihydroxy-3-methyl-1-pentene, 5,6-dihydroxy-1-hexene, 4-hydroxy-1-hexene, 5-hydroxy-1-hexene, 6-hydroxy-1-hexene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene and 5,6-diacyloxy-1-hexene. Among them, propylene, 3-acetoxy-1-propylene, 3-acetoxy-1-butene, 4-acetoxy-1-butene and 3,4-diacetoxy-1-butene are preferred from the viewpoint of copolymerization reactivity and gas barrier properties of the obtained multilayer structure. In the case of an olefin having an ester, the above structural unit (I) is derived during the saponification reaction.

[0073] In the above structural unit (II), preferably R4 and R 5 are all hydrogen atoms. In particular, more preferred are: R 4 and R 5 are all hydrogen atoms, and the above R 6 and R 7 One of them is an aliphatic hydrocarbon group having 1 to 10 carbon atoms, and the other is a hydrogen atom. The aliphatic hydrocarbon group is preferably an alkyl group or an alkenyl group. From the viewpoint of attaching particular importance to the gas barrier properties of the obtained multilayer structure, it is particularly preferred that: R 6 and R 7 One of them is a methyl group or an ethyl group, and the other is a hydrogen atom. In addition, it is particularly preferred that: 6 and R 7 One of them is (CH2) h OH (wherein h is an integer from 1 to 8), and the other is a hydrogen atom. h In the substituent represented by OH, h is preferably an integer of 1 to 4, more preferably 1 or 2, and particularly preferably 1.

[0074] The method for making EVOH (a1) contain the structural unit (II) is not particularly limited, and a method of making EVOH obtained by saponification reaction react with a monovalent epoxy compound can be used. As the monovalent epoxy compound, the compounds represented by the following formulas (IV) to (X) can be used appropriately.

[0075] [Chemistry 2]

[0076]

[0077] In the above formulas (IV) to (X), R 14 , R 15 , R 16 , R 17 and R 18 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms (such as an alkyl group and an alkenyl group), an alicyclic hydrocarbon group having 3 to 10 carbon atoms (such as a cycloalkyl group and a cycloalkenyl group), or an aliphatic hydrocarbon group having 6 to 10 carbon atoms (such as a phenyl group). In addition, i, j, k, p, and q each independently represent an integer of 1 to 8.

[0078] Examples of the monovalent epoxy compound represented by the formula (IV) include ethylene oxide (ethylene oxide), propylene oxide, 1,2-butylene oxide, 2,3-butylene oxide, 3-methyl-1,2-butylene oxide, 1,2-pentene oxide, 3-methyl-1,2-pentene oxide, 1,2-hexene oxide, 2,3-hexene oxide, 3,4-hexene oxide, 3-methyl-1,2-hexene oxide, 3-methyl-1,2-epoxyheptane, 4-methyl-1,2-epoxyheptane, 1,2-octane oxide, 2,3-octane oxide, 1,2-nonane oxide, 2,3-nonane oxide, 1,2-decane oxide, 1,2-dodecane oxide, ethylbenzene oxide, 1-phenyl-1,2-epoxypropylene, and 3-phenyl-1,2-epoxypropylene. As the monocyclic epoxy compound represented by the above formula (V), various alkyl glycidyl ethers and the like can be listed. As the monocyclic epoxy compound represented by the above formula (VI), various alkylene glycol monoglycidyl ethers can be listed. As the monocyclic epoxy compound represented by the above formula (VII), various alkenyl glycidyl ethers can be listed. As the monocyclic epoxy compound represented by the above formula (VIII), various oxirane alcohols such as glycidol can be listed. As the monocyclic epoxy compound represented by the above formula (IX), various epoxy cycloalkanes can be listed. As the monocyclic epoxy compound represented by the above formula (X), various epoxy cycloolefins can be listed.

[0079] Among the above-mentioned monocyclic epoxy compounds, epoxy compounds having 2 to 8 carbon atoms are preferred. In particular, from the viewpoint of the ease of handling and reactivity of the compound, the number of carbon atoms of the monocyclic epoxy compound is more preferably 2 to 6, and further preferably 2 to 4. In addition, the monocyclic epoxy compound is particularly preferably a compound represented by formula (IV) and a compound represented by formula (V) among the above-mentioned formulas. Specifically, from the viewpoint of reactivity with EVOH (a1) and gas barrier properties of the obtained multilayer structure, 1,2-butylene oxide, 2,3-butylene oxide, propylene oxide, ethylene oxide and glycidol are preferred, among which propylene oxide and glycidol are particularly preferred.

[0080] In the above structural unit (III), R 8 , R 9 , R 10 and R 11 It is preferably a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms. In particular, the aliphatic hydrocarbon group is preferably a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, and a pentyl group.

[0081] The method for making EVOH (a1) contain the structural unit (III) is not particularly limited, and for example, it can be produced by the method described in Japanese Patent Application Laid-Open No. 2014-034647.

[0082] <Thermoplastic resin (a2)>

[0083] Thermoplastic resin (a2) is a thermoplastic resin having a functional group capable of reacting with EVOH (a1). The functional group is preferably a group that reacts with the hydroxyl group of EVOH (a1). Specific examples of the functional group include, for example, a carboxyl group or a derivative thereof, a phosphoric acid group or a derivative thereof, an epoxy group, an amino group, a halogen, etc. As a derivative of the carboxyl group, a carboxylic acid anhydride group (-CO-O-CO-), a carboxylic acid chloride group (-COCl, -COBr, etc.), etc., can be listed. Among these, acidic groups such as carboxyl groups, phosphoric acid groups or their derivatives are preferred, and carboxyl groups or their derivatives are more preferred. It should be noted that the acidic group may exist in the form of a salt.

[0084] As thermoplastic resin (a2), a modified thermoplastic resin containing a carboxyl group obtained by chemically bonding an olefinic unsaturated carboxylic acid or its anhydride (e.g., addition reaction, grafting reaction, copolymerization, etc.) to a thermoplastic resin can be appropriately used. As a thermoplastic resin into which a functional group (modifying group) is introduced, an olefin polymer can be appropriately used. As an olefin polymer, polyolefins such as polyethylene, polypropylene, and polybutene can be used; copolymers of olefins and other monomers (vinyl esters, unsaturated carboxylates, styrene, etc.) (e.g., ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, SEBS (hydrogenated products of block copolymers of styrene and butadiene), etc.) etc. Among them, polyethylene, polypropylene, ethylene-vinyl acetate copolymers (the content of vinyl acetate is 5 to 55% by mass) and ethylene-ethyl acrylate copolymers (the content of ethyl acrylate is 8 to 35% by mass) are preferably used, polyethylene, polypropylene, and ethylene-vinyl acetate copolymers are more preferably used, and polyethylene and polypropylene are particularly preferably used.

[0085] As the ethylenically unsaturated carboxylic acid or its anhydride, ethylenically unsaturated monocarboxylic acid or its ester, ethylenically unsaturated dicarboxylic acid or its monoester or diester, or its anhydride, among which ethylenically unsaturated dicarboxylic acid anhydride is preferred. Specifically, maleic acid, fumaric acid, itaconic acid, maleic anhydride, itaconic anhydride, monomethyl maleate, monoethyl maleate, diethyl maleate, monomethyl fumarate, etc. can be listed, and maleic anhydride is particularly suitable.

[0086] Like this, thermoplastic resin (a2) is preferably a modified olefin polymer, more preferably a modified polyethylene, a modified polypropylene, a modified ethylene-vinyl acetate copolymer and a modified ethylene-ethyl acrylate copolymer. In addition, it is also preferably a modified polyolefin, and more preferably a modified polyethylene and a modified polypropylene. These modified olefin polymers, modified polyolefins, modified polyethylene, modified polypropylene, modified ethylene-vinyl acetate copolymers and modified ethylene-ethyl acrylate copolymers are preferably acid-modified, more preferably carboxylic acid-modified, respectively. These thermoplastic resins (a2) can be used alone or in combination of two or more.

[0087] The thermoplastic resin (a2) may preferably have a 100% modulus of 6 MPa or more at -30°C. If the 100% modulus of the thermoplastic resin (a2) at -30°C is less than 6 MPa, solvent resistance and the like may be affected.

[0088] The amount of addition or grafting of the functional group (modifying group) to the thermoplastic resin (modification degree) is 0.0001 to 15% by mass, preferably 0.001 to 10% by mass, relative to the unmodified thermoplastic resin. The addition reaction or grafting reaction of the functional group (modifying group) to the thermoplastic resin can be carried out by, for example, a free radical polymerization method in the presence of a solvent (xylene, etc.) and a catalyst (peroxide, etc.).

[0089] The lower limit of the melt flow rate (MFR) of the thermoplastic resin (a2) measured at 190°C and a load of 2160g is preferably 0.2g / 10min, more preferably 0.5g / 10min, and further preferably 1.5g / 10min. On the other hand, the upper limit of the MFR is preferably 1100g / 10min, more preferably 900g / 10min, and further preferably 800g / 10min. By setting the MFR of the thermoplastic resin (a2) to the above range, the dispersibility becomes good, and therefore, there is a tendency for gas barrier properties, interlayer adhesion, recyclability, solvent resistance, etc. to become better.

[0090] The acid value of the thermoplastic resin (a2) is preferably 0.5 mgKOH / g or more, more preferably 5 mgKOH / g or more, and further preferably 15 mgKOH / g or more. The acid value of the thermoplastic resin (a2) is preferably 100 mgKOH / g or less, more preferably 50 mgKOH / g or less, and further preferably 40 mgKOH / g or less. If the acid value of the thermoplastic resin (a2) is 0.5 mgKOH / g or more, the swelling degree of the A layer is reduced, and therefore, there is a tendency for the solvent resistance (resistance to interlayer delamination) to be improved. In addition, if the acid value of the thermoplastic resin (a2) is 100 mgKOH / g or less, there is a tendency for the dispersibility of the thermoplastic resin to be improved, the interlayer adhesion, the recyclability, etc. to be improved. It should be noted that the acid value of the thermoplastic resin (a2) can be measured based on JIS K 0070 (1992).

[0091] The content of the thermoplastic resin (a2) in the A layer is more than 0.1 mass parts relative to the total 100 mass parts of EVOH (a1) and thermoplastic resin (a2), preferably more than 1 mass part, more preferably more than 3 mass parts. In addition, the content of the thermoplastic resin (a2) is less than 30 mass parts relative to the total 100 mass parts of EVOH (a1) and thermoplastic resin (a2), preferably less than 20 mass parts, more preferably less than 15 mass parts. If the content of the thermoplastic resin (a2) is less than 0.1 mass parts, there is a tendency that the resistance to solvent resistance is low and the interlayer peeling when exposed in an organic solvent becomes insufficient. In addition, if the content of the thermoplastic resin (a2) exceeds 30 mass parts, the following tendency is presented: the appearance of the multilayer structure of the present invention, the gas barrier property deteriorates, and in addition, the rotation torque variation of the extruder screw during the melt forming is also increased in order to reuse the scraps of the multilayer structure of the present invention, etc.

[0092] The A layer preferably forms a phase-separated structure having a sea phase and an island phase. It is preferred that the sea phase contains EVOH (a1) and the island phase contains a thermoplastic resin (a2).

[0093] When the A layer forms the above-mentioned phase separation structure with the sea-island structure, the dispersed particle size of the island phase is preferably 1 μm or less, more preferably less than 0.5 μm, and further preferably less than 0.4 μm or less than 0.3 μm. The dispersed particle size of the island phase can be 0.1 μm or more. As means for adjusting the dispersed particle size, for example, a method of adjusting the acid value of the thermoplastic resin (a2) can be listed. In addition, it is preferred that a phase containing EVOH (a1) is also provided inside the aforementioned island phase, and more preferably EVOH (a1) is dispersed in a scattered point shape. When the aforementioned island phase also has a phase containing EVOH (a1), its dispersed particle size is preferably 0.5 μm or less, more preferably less than 0.3 μm, and can be 0.005 μm or more. As means for adjusting the dispersed particle size of the phase containing EVOH (a1), for example, a method of adjusting the film forming conditions when the multilayer structure is formed into a film can be listed. If a phase containing EVOH (a1) is formed inside the island phase containing the thermoplastic resin (a2), the recyclability of the A layer can be improved.

[0094] <Higher fatty acid metal salt (a3)>

[0095] The A layer preferably contains a higher fatty acid metal salt (a3). The content of the higher fatty acid metal salt (a3) ​​in the A layer is preferably more than 10ppm and less than 300ppm in terms of metal atom conversion. Here, the "higher fatty acid" in this specification refers to a fatty acid with a carbon number of more than 10. In addition, in this specification, "ppm" is a mass-based content. By making the A layer contain a higher fatty acid metal salt (a3), when melt molding is implemented again in order to reuse scraps, etc., the deterioration of hue and the amount of adhesion of degraded resin to the screw in the melt molding machine can be reduced, so it is preferred. It should be noted that if the amount of adhesion of degraded resin to the screw in the melt molding machine is small, the rotational torque changes little, and molding can be carried out stably for a long time.

[0096] As the metal atom constituting the higher fatty acid metal salt (a3), it can be a single metal species, or it can contain multiple metal species. As the metal atom, it is preferably a divalent metal. Among them, it is preferably included at least one selected from magnesium, manganese, tin, cobalt, zinc, cadmium, lead and titanium, and more preferably includes at least one selected from magnesium, cobalt, tin and titanium. Among them, it is preferably included magnesium or cobalt. By including the above-mentioned metal atoms, there is a tendency for layer A and layer B to show higher adhesion. The reason for showing high adhesion is still uncertain, but there is a tendency that the compound containing the above-mentioned metal atoms will promote the transesterification reaction, and it can be considered that the reaction helps to improve the possibility of adhesion.

[0097] The lower limit of the carbon number of the higher fatty acid constituting the higher fatty acid metal salt (a3) ​​is preferably 12, more preferably 13, and further preferably 14, 15, 16, 17 and 18. In addition, the upper limit of the carbon number is, for example, 30, can be 24, can also be 22, can also be 20. As the higher fatty acid constituting the higher fatty acid metal salt (a3), stearic acid, ricinoleic acid, myristic acid, lauric acid, etc. can be listed, wherein, stearic acid is preferably. By including the above-mentioned higher fatty acid, there is a tendency that can suppress the deterioration of hue, so it is preferred.

[0098] As the higher fatty acid metal salt (a3), for example, magnesium stearate, cobalt stearate, etc. can be suitably used.

[0099] The content of the higher fatty acid metal salt (a3) ​​is preferably more than 10ppm in terms of metal atom conversion, more preferably more than 20ppm, and further preferably more than 30ppm. In addition, the content of the higher fatty acid metal salt (a3) ​​is preferably less than 300ppm in terms of metal atom conversion, more preferably less than 200ppm, and further preferably less than 100ppm. If the content of the higher fatty acid metal salt (a3) ​​is more than 10ppm in terms of metal atom conversion, there is a tendency to improve interlayer adhesion, recyclability, etc. In addition, if the content of the higher fatty acid metal salt (a3) ​​is less than 300ppm in terms of metal atom conversion, there is a tendency to suppress the deterioration of hue and recyclability.

[0100] One or more additives selected from phosphoric acid compounds, carboxylic acids, boron compounds, metal salts other than higher fatty acid metal salts (a3), etc. may be added to layer A within a range that does not impair the effects of the present invention. By adding these additives to EVOH (a1) etc. constituting layer A, various properties of the obtained multilayer structure can be improved.

[0101] As the phosphate compound, various acids such as phosphoric acid and phosphorous acid or their salts can be used. The phosphate can be in any form of dihydrogen phosphate, monohydrogen phosphate and phosphate. The cationic species of the phosphate is not particularly limited, and the cationic species is preferably an alkali metal or an alkaline earth metal. Among them, the phosphate compound is preferably added in the form of sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate or dipotassium hydrogen phosphate. When the A layer contains the phosphate compound, its content is preferably 1 to 500 ppm in terms of phosphate radical conversion. If the A layer contains the phosphate compound, there is a tendency that the long-term operability of the A layer is improved when the film is formed for a long time.

[0102] The carboxylic acids contained in the A layer may be carboxylate ions or carboxylic acid derivatives in addition to carboxylic acids. In addition, the carboxylic acid may be a monocarboxylic acid, a polycarboxylic acid having two or more carboxyl groups in the molecule, or a combination thereof. It should be noted that the polycarboxylic acid does not include a polymer. In addition, the polycarboxylate ion is formed by the detachment of at least one hydrogen ion of the carboxyl group of the polycarboxylic acid. The carboxyl group of the carboxylic acid may be esterified, and the carboxylate ion may form a salt with a metal. The carbon number of the carboxylic acid is preferably less than 10.

[0103] As monocarboxylic acid, there is no particular limitation, and examples thereof include formic acid, acetic acid, propionic acid, butyric acid, caproic acid, capric acid, acrylic acid, methacrylic acid, benzoic acid, 2-naphthoic acid, etc. These carboxylic acids may have a hydroxyl group or a halogen atom. In addition, as carboxylate ions, ions formed by the detachment of the hydrogen ions of the carboxyl groups of the above-mentioned carboxyl groups may be listed. As the pKa of the monocarboxylic acid (also including monocarboxylic acids providing monocarboxylate ions), from the viewpoints of the pH adjustment ability and melt formability of the composition, it is preferably 3.5 or more, and more preferably 4 or more. As such monocarboxylic acids, formic acid (pKa=3.68), acetic acid (pKa=4.74), propionic acid (pKa=4.85), butyric acid (pKa=4.80), etc. may be listed, and from the viewpoints of ease of handling, acetic acid is preferably used.

[0104] In addition, as a polyvalent carboxylic acid, as long as there are more than two carboxyl groups in the molecule, there is no particular limitation, and examples thereof include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, and pimelic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; tricarboxylic acids such as aconitic acid; carboxylic acids having more than four carboxyl groups such as 1,2,3,4-butanetetracarboxylic acid and ethylenediaminetetraacetic acid; hydroxycarboxylic acids such as tartaric acid, citric acid, isocitric acid, malic acid, mucic acid, succinic acid, and citramalic acid; ketocarboxylic acids such as oxaloacetic acid, pyruvic acid, 2-ketoglutaric acid, and 3-ketoglutaric acid; amino acids such as glutamic acid, aspartic acid, and 2-aminoadipic acid. It should be noted that as polyvalent carboxylate ions, their anions can be listed. Among them, from the viewpoint of easy acquisition, succinic acid, malic acid, tartaric acid, and citric acid are particularly preferred.

[0105] When the layer A contains carboxylic acids, the content thereof is preferably 0.5 μmol / g to 20 μmol / g in terms of carboxylate radical from the viewpoint of coloration resistance during melt molding.

[0106] Examples of the boron compound include boric acids, boric esters, borate salts, boron hydrides, etc. Specifically, examples of the boric acid include orthoboric acid (hereinafter also referred to as "boric acid"), metaboric acid, tetraboric acid, etc., examples of the boric ester include triethyl borate, trimethyl borate, etc., and examples of the borate salt include alkali metal salts, alkaline earth metal salts, borax, etc. of the aforementioned various boric acids. Among these compounds, orthoboric acid is preferred.

[0107] When the layer A contains a boron compound, the content thereof is preferably 20 to 2000 ppm in terms of boron element conversion from the viewpoint of improving the film formation stability of the layer A.

[0108] As metal salts other than higher fatty acid metal salts (a3), metal salts of lower fatty acids having a carbon number of less than 10, metal salts of organic acids other than fatty acids, metal salts of inorganic acids, etc. can be listed. As the metal used in the metal salt, an alkali metal or an alkaline earth metal is preferred. As alkali metals, lithium, sodium, potassium, etc. can be listed, and as alkali metal salts, lower aliphatic carboxylates, aromatic carboxylates, phosphates, metal complexes, etc. of alkali metals can be listed. For example, sodium acetate, potassium acetate, sodium phosphate, potassium phosphate, sodium salt of ethylenediaminetetraacetic acid, etc. can be listed, among which sodium acetate, potassium acetate, sodium phosphate and potassium phosphate are suitable. When the A layer contains an alkali metal salt other than the higher fatty acid metal salt (a3), from the viewpoint of improving interlayer adhesion, its content is preferably 20~1000ppm in terms of metal atom conversion. As alkaline earth metals, beryllium, magnesium, calcium, strontium, barium, etc. can be listed, and from the viewpoint of industrial acquisition, magnesium or calcium is more preferred. As alkaline earth metal salts, lower aliphatic carboxylates, aromatic carboxylates, phosphates, metal complexes of alkaline earth metals, etc. can be listed. For example, magnesium acetate, calcium acetate, magnesium phosphate, calcium phosphate, etc. can be listed, among which magnesium acetate and calcium acetate are suitable. When layer A contains alkaline earth metal salts other than higher fatty acid metal salts (a3), its content is preferably 20~1000ppm in terms of metal atom conversion. By containing alkaline earth metal salts in the above range, there is a tendency that layer A and layer B show higher adhesion. In addition, the deterioration of EVOH during repeated reuse of the multilayer structure is suppressed, and the appearance of the molded product is improved due to the reduction of defects such as gels and particles.

[0109] The A layer may contain other resins in addition to EVOH (a1) and thermoplastic resin (a2) within the range that does not impair the effects of the present invention. Examples of such other resins include polyethylene, polypropylene, ethylene-propylene copolymers, ethylene or propylene copolymers (copolymers of ethylene or propylene with at least one of the following monomers: α-olefins such as 1-butene, isobutylene, 4-methyl-1-pentene, 1-hexene, 1-octene, etc.; vinyl pyrrolidones, etc.), polyolefins such as poly-4-methyl-1-pentene and poly-1-butene; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyvinylidene chloride, polyvinyl chloride, polystyrene, polycarbonate, and polyacrylate, etc.

[0110] In addition, in addition to the other resins mentioned above, layer A may also contain various ingredients such as heat stabilizers, ultraviolet absorbers, antioxidants, colorants, fillers, plasticizers, photoinitiators, deodorants, antistatic agents, lubricants, desiccants, fillers, pigments, dyes, processing aids, flame retardants, antifogging agents, etc.

[0111] 〈B layer〉

[0112] The B layer is a polyurethane layer containing TPU (b). The multilayer structure of the present invention can exert good stretchability, bending resistance, thermoformability, etc. by having a B layer containing TPU (b). The swelling degree of the B layer when immersed for 30 minutes at 40°C and 1-propanol / water = 60 / 40% by mass is preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 20% by mass or less. In addition, the swelling degree of the B layer can be 5% by mass or more. By making the swelling degree of the B layer within the above range, the following tendency is presented: it is close to the swelling degree of the A layer, and the interlayer peeling of the multilayer structure can be suppressed even when immersed in an organic solvent. It should be noted that the swelling degree of the B layer can be measured by the method described in the embodiment. In addition, the difference between the swelling degrees of the A layer and the B layer is preferably 35% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, and particularly preferably 15% by mass or less. When the difference in swelling degree is within the above range, there is a tendency that interlayer delamination of the multilayer structure when immersed in an organic solvent can be further suppressed.

[0113] If the B layer contains TPU (b), it is preferred because stretchability and thermoformability can be improved. In addition, in the multilayer structure of the present invention, due to the adhesion between the B layer and the A layer, good bending resistance can be exhibited.

[0114] The content of TPU (b) in the B layer is also preferably 60 mass % or more, more preferably 80 mass % or more, further preferably 90 mass % or more, further preferably 95 mass % or more, further preferably 99 mass % or more, and may be 100 mass %.

[0115] TPU (b) is composed of a polymer polyol, an organic polyisocyanate, a chain extender, etc. Typically, TPU (b) is a linear multi-block copolymer of (1) a hard segment obtained by the reaction of a short-chain diol (low-molecular polyol) and an isocyanate and (2) a soft segment obtained by the reaction of a long-chain diol (polymer polyol) and an isocyanate.

[0116] High molecular weight polyol is a substance having multiple hydroxyl groups, obtained by polycondensation, addition polymerization (e.g., ring-opening polymerization), polyaddition, etc. As high molecular weight polyol, for example, polyester polyol, polyether polyol, polycarbonate polyol or their co-condensates (e.g., polyester-ether-polyol) etc. can be listed. These high molecular weight polyols can be used alone or in combination of two or more. However, polyester polyol and polycarbonate polyol are preferred, and polyester polyol is particularly preferred.

[0117] The polyester polyol can be produced, for example, by directly condensing an ester-forming derivative such as a dicarboxylic acid, an ester thereof or an anhydride thereof with a low-molecular polyol through an esterification reaction or an ester exchange reaction, or by ring-opening polymerization of a lactone according to a conventional method.

[0118] Examples of the polyether polyol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, poly(methyltetramethylene) glycol, etc. These polyether polyols may be used alone or in combination of two or more. Among them, polytetramethylene glycol is preferred.

[0119] As the polycarbonate polyol, for example, one obtained by polycondensing an aliphatic diol having 2 to 12 carbon atoms such as 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, or a mixture thereof with diphenyl carbonate or phosgene is preferably used.

[0120] The lower limit of the number average molecular weight of the above-mentioned polymer polyol is preferably 500, more preferably 600, and further preferably 700. On the other hand, the upper limit of the number average molecular weight of the polymer polyol is preferably 8,000, more preferably 5,000, and further preferably 3,000. By setting the number average molecular weight of the polymer polyol to above the above lower limit, the compatibility with the organic polyisocyanate becomes moderate, the elasticity of the obtained TPU is improved, and therefore, the mechanical properties such as the stretchability of the obtained multilayer structure and the tendency of improved thermoforming are presented. On the contrary, by setting the number average molecular weight of the polymer polyol to below the above upper limit, the compatibility with the organic polyisocyanate is improved, and it is easy to mix during the polymerization process. As a result, the generation of gel blocks is sometimes suppressed, and stable TPU is easily obtained. It should be noted that the number average molecular weight of the polymer polyol is measured in accordance with JIS K1577 and the number average molecular weight calculated based on the hydroxyl value.

[0121] As organic polyisocyanate, it is not particularly limited, and the known organic diisocyanate commonly used in the manufacture of TPU can be used, for example, 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, benzene diisocyanate, xylylene diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dichloro-4,4'-diphenylmethane diisocyanate, distyrene diisocyanate and other aromatic diisocyanates; hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hydrogenated xylylene diisocyanate and other aliphatic diisocyanates (including alicyclic diisocyanates) and the like. Among them, from the viewpoint that the strength and bending resistance of the obtained multilayer structure can be improved, preferably 4,4'-diphenylmethane diisocyanate. These organic diisocyanates can be used alone or in combination of two or more.

[0122] As a chain extender, a chain extender commonly used in the manufacture of TPU can be used, and a low molecular weight compound having two or more active hydrogen atoms capable of reacting with an isocyanate group and a molecular weight of 300 or less can be appropriately used. As a chain extender, for example, ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-bis(β-hydroxyethoxy)benzene, 1,4-cyclohexanediol, etc. can be listed. Among them, from the viewpoint of better stretchability and thermoformability of the obtained multilayer structure, aliphatic diols having 2 to 10 carbon atoms are preferred, and 1,4-butanediol is particularly preferred. These chain extenders can be used alone or in combination of two or more.

[0123] As a method for producing TPU (b), the above-mentioned high molecular weight polyol, organic polyisocyanate and chain extender can be used to produce it by using a known urethanization reaction technology, or it can be produced by using any of a prepolymer method and a one-step method. Among them, it is preferred to carry out melt polymerization in the substantial absence of a solvent, and it is particularly preferred to carry out continuous melt polymerization using a multi-screw extruder.

[0124] The B layer may be composed of TPU (b) alone, or may contain other resins in addition to TPU (b). In addition to the other resins mentioned above, the B layer may further contain other components such as heat stabilizers, ultraviolet absorbers, antioxidants, colorants, antistatic agents, lubricants, fillers, etc. It should be noted that the suitable form of the B1 layer and the B2 layer is the same as the suitable form of the B layer except for the average thickness.

[0125] 〈D Floor〉

[0126] The D layer is a protective layer directly laminated on the B2 layer and is a layer containing TPU (x). If the multilayer structure of the present invention includes the D layer, it tends to have improved durability and flexibility and to be able to maintain good gas barrier properties after bending. The suitable form of TPU (x) is the same as the suitable form of TPU (b) as a component of the B layer except for the content. The content of TPU (x) in the D layer is preferably 70% by mass or more and 99% by mass or less, and more preferably 80% by mass or more and 98% by mass or less.

[0127] The D layer preferably contains EVOH (y). If the D layer contains EVOH (y), there is a tendency that the gas barrier properties after bending can be well maintained. The suitable form of EVOH (y) is the same as the suitable form of EVOH (a1) as a component of the A layer except for the content. The content of EVOH (y) in the D layer is preferably 1% by mass or more and 30% by mass or less, and more preferably 2% by mass or more and 20% by mass or less.

[0128] The D layer preferably contains a thermoplastic resin (z). If the D layer contains a thermoplastic resin (z), there is a tendency that solvent resistance and durability become good. The suitable form of the thermoplastic resin (z) is the same as the suitable form of the thermoplastic resin (a2) as the A layer component except for the content. The content of the thermoplastic resin (z) in the D layer is preferably 0.001% by mass or more and 10% by mass or less, more preferably 0.01% by mass or more and 7% by mass or less, and further preferably 0.03% by mass or more and 4% by mass or less.

[0129] From the viewpoint of cost reduction, the D layer is preferably a layer obtained by using recycled materials such as scraps and defective products of the multilayer structure of the present invention.

[0130] As a method for using the scraps, defective products and other recyclables of the multilayer structure of the present invention, there is the following method: the scraps and defective products are crushed and then put into an extruder for film making; or, after melt mixing in an extruder to make pellets, the pellets are put into an extruder again for film making. In order to control the thickness of the D layer, or in order to dilute with new TPU, it is preferred to melt mix and make pellets, and then put the pellets into an extruder again for film making.

[0131] The content ratio x / y of TPU (x) to EVOH (y) in the D layer is preferably 70 / 30 or more, more preferably 75 / 25 or more, and further preferably 80 / 20 or more. On the other hand, the content ratio x / y is preferably 100 / 0 or less, more preferably 99 / 1 or less, and further preferably 98 / 2 or less. When the content ratio x / y is within the above range, sufficient flexibility is exhibited, and there is a tendency that the gas barrier properties after bending can be well maintained.

[0132] The total amount of TPU (x) and EVOH (y) constituting the D layer is preferably 80% by mass or more, more preferably 85% by mass or more, and further preferably 90% by mass or more. If the total amount of TPU (x) and EVOH (y) constituting the D layer is 80% by mass or more, the gas barrier properties after bending can be maintained, and sufficient flexibility can be easily exhibited. The total amount of TPU (x) and EVOH (y) constituting the D layer may be 99% by mass or more.

[0133] 〈Purpose, etc.〉

[0134] The multilayer structure of the present invention has excellent interlayer adhesion, gas barrier properties, appearance, bending resistance, solvent resistance, etc., and can therefore be used for food packaging materials, medical container packaging materials, other container packaging materials, industrial sheets, etc., building material sheets, agricultural sheets, geological treatment films, radon barrier films, other sheets, other various pipes, etc. In particular, the multilayer structure of the present invention can be suitably used as a gas barrier film laminated on a film-like rubber product such as a tire inner liner, a shoe sole air cushioning material, an accumulator inner bag, an inflatable ball, and an air spring.

[0135] <Method for producing multilayer structure>

[0136] The method for producing the multilayer structure of the present invention is not particularly limited as long as it is a method for laminating and bonding the A layer and the B layer in a satisfactory manner, and a known method such as coextrusion, lamination, coating, bonding, and attachment may be employed.

[0137] The multilayer structure of the present invention can be preferably produced by a production method including a step of coextruding a resin forming layer A and a resin forming layer B. This production method has high productivity, can obtain excellent interlayer adhesion between layer A and layer B, and is also excellent in recyclability.

[0138] In the multilayer co-extrusion method, the resin forming the A layer and the resin forming the B layer are heated and melted, and are supplied to the extrusion die from different extruders and pumps through their respective flow paths, and are extruded from the extrusion die into multiple layers, and then laminated and bonded to form the multilayer structure of the present invention. As the extrusion die, for example, a multi-manifold die, a feed block, a static mixer, etc. can be used.

[0139] It should be noted that the relationship between the viscosities of the resins forming the A layer and the B layer is preferably the following melt viscosity ratio. That is, the melt viscosity (η) of the resin forming the A layer at a temperature of 210°C and a shear rate of 1,000 / sec is: A ) and the melt viscosity (η) of the resin forming the B layer B ) ratio (η B / η A The lower limit of ) is preferably 0.3, more preferably 0.5. On the other hand, the melt viscosity ratio (η B / η A The upper limit of ) is preferably 2, more preferably 1.5. B / η A ) is set to the above-mentioned range, so that in the molding of the multilayer structure of the present invention based on the multilayer co-extrusion method, the appearance becomes good, and in addition, the adhesion between layer A and layer B becomes good, which can improve the durability of the multilayer structure of the present invention.

[0140] When the multilayer structure of the present invention has a layer other than layer A and layer B, such as layer D, it can also be manufactured according to the above method. That is, each layer can be laminated by a known method such as coextrusion, pasting, coating, bonding, and adhesion, among which coextrusion is preferred.

[0141] The method for producing a multilayer structure of the present invention may include a step of irradiating the structure (multilayer structure) obtained by coextrusion with electron beams. By irradiating electron beams, a crosslinking reaction between layers occurs, and the interlayer adhesion of the obtained multilayer structure can be improved. As an electron beam source, various electron beam accelerators such as Cockcroft-Walton type, Van de Graaff type, resonance transformer type, insulating core transformer type, high frequency high voltage type, and high frequency type can be used.

[0142] 〈molded body〉

[0143] The molded body described in one embodiment of the present invention has the multilayer structure of the present invention. In the molded body of the present invention, it is preferred that at least one of the A layer and the B layer contains a colorant. As the molded body, a container, a tube, a sheet, a bag, a gas-filled cushioning material, etc. can be listed, preferably a gas-filled cushioning material. The gas-filled cushioning material is formed by forming the multilayer structure of the present invention into a bag-like shape of a prescribed shape and filling it with gas. The gas-filled cushioning material can be suitably used as, for example, a cushioning material for shoes (sole air cushioning material), etc.

[0144] The molded article of the present invention may be composed only of the multilayer structure of the present invention, or may further include components other than the multilayer structure of the present invention. For example, other resin layers may be further laminated on the multilayer structure of the present invention, and the laminate may be molded into a predetermined shape.

[0145] The colorant contained in at least one of the A layer and the B layer of the multilayer structure constituting the molded body of the present invention may be any of a pigment and a dye, or may be a white or black colorant. In the molded body of the present invention, when at least one of the A layer and the B layer contains a colorant, the design is excellent. The colorant may be contained only in a part of the A layer or the B layer. That is, a graphic, a text, etc. may be applied by using a colorant. On the other hand, at least one of the A layer and the B layer may contain a colorant as a whole, and the multilayer structure as a whole may be colored in a specified color.

[0146] The molded article of the present invention uses the multilayer structure of the present invention having excellent gas barrier properties and bending resistance, and therefore, when it is a cushioning material filled with gas, its cushioning properties can be continuously exerted for a long time. In addition, the multilayer structure of the present invention has excellent solvent resistance, and therefore, the molded article of the present invention can also be used in applications that come into contact with solvents, and even the product obtained after a process of coming into contact with solvents can also exert good performance.

[0147] <Method for producing molded article>

[0148] The method for producing the molded body of the present invention is not particularly limited, and preferably comprises a step (A) of contacting the multilayer structure with a treatment liquid containing an organic solvent. The treatment liquid preferably contains a colorant. In addition, the method for producing the molded body of the present invention may further comprise a step (B) of molding the multilayer structure. The order of the steps (A) and (B) is not particularly limited, and preferably the steps (A) and (B) are carried out in that order.

[0149] According to the method for producing a molded body of the present invention, coloring is performed by bringing a treatment liquid containing a colorant and an organic solvent into contact with the multilayer structure in step (A), thereby impregnating the colorant into at least one of layer A and layer B of the multilayer structure. The contact of the treatment liquid with the multilayer structure can be performed by immersing the multilayer structure in the treatment liquid, applying the treatment liquid, printing the treatment liquid, etc.

[0150] The organic solvent contained in the treatment liquid is not particularly limited, as long as it is a liquid that can fully dissolve or disperse the colorant. Examples of the organic solvent include alcohols such as methanol and ethanol; esters such as ethyl acetate and butyl acetate; ethers such as diethyl ether and ethylene glycol monobutyl ether; ketones such as acetone and cyclohexanone; aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene. The treatment liquid may further contain other components such as water and a surfactant.

[0151] In the manufacturing method of the present invention, the multilayer structure is colored using a treatment liquid containing an organic solvent, but the multilayer structure has excellent solvent resistance, so high interlayer adhesion can be maintained even after the coloring treatment. That is, in the manufacturing process, although the multilayer structure is exposed to an organic solvent, a molded body with excellent interlayer delamination resistance can be obtained. In addition, for example, for an uncolored multilayer structure, it is possible to implement coloring using a variety of treatment liquids to achieve various changes, so that the productivity is excellent.

[0152] As another embodiment, in the method for manufacturing a molded body of the present invention, the treatment liquid used in step (A) may not contain a colorant. For example, in step (A), a treatment liquid containing an adhesive and an organic solvent may be brought into contact with the multilayer structure to bond the multilayer structure to other components. In this way, even when an organic solvent-based adhesive is used, the multilayer structure of the present invention has excellent solvent resistance, so interlayer delamination is unlikely to occur, and good bonding and molding can be performed. Example

[0153] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the following Examples.

[0154] <Materials used>

[0155] (EVOH(a1))

[0156] ・EVOH-1: "Eval (registered trademark) E105B" (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer, ethylene unit content: 44 mol%)

[0157] ・EVOH-2: "Eval (registered trademark) F101B" (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer, ethylene unit content: 32 mol%)

[0158] ・EVOH-3: "Eval (registered trademark) L171B" (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer, ethylene unit content: 27 mol%)

[0159] ・EVOH-4: "Eval (registered trademark) G156B" (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer, ethylene unit content: 48 mol%)

[0160] (Thermoplastic resin (a2))

[0161] ・a2-1: "Scona (registered trademark) TPPP2112GA" (manufactured by Big Chemie Japan Co., Ltd., maleic anhydride-modified polypropylene (PP), acid value: 21.8 mgKOH / g)

[0162] ・a2-2: "Modek (registered trademark) P908" (manufactured by Mitsubishi Chemical Corporation, maleic anhydride-modified PP, acid value 16.9 mgKOH / g)

[0163] ・a2-3: "PRIEX (registered trademark) 25097" (manufactured by Addcomp, maleic anhydride-modified PP, acid value 12.1 mgKOH / g)

[0164] ・a2-4: "Admer (registered trademark) QE840" (Mitsui Chemicals, maleic anhydride-modified PP, acid value 1.8 mgKOH / g)

[0165] ・a2-5: "Rikeide MG440P" (manufactured by Riken Biomin Co., Ltd., maleic anhydride-modified PP, acid value 49.6 mgKOH / g)

[0166] ・a2-6: "Yumax 1010" (manufactured by Sanyo Chemical Industries, Ltd., maleic anhydride-modified PP, acid value 81.1 mgKOH / g)

[0167] ・a2-7: "LOTADER (registered trademark) 3210" (manufactured by Tokyo Materials Co., Ltd., maleic anhydride-modified ethylene-ethyl acrylate copolymer, acid value: 17.4 mgKOH / g)

[0168] ・a2-8: "Admer (registered trademark) PF508" (Mitsui Chemicals, maleic anhydride-modified PP + maleic anhydride-modified PE (polyethylene), acid value 6.7 mgKOH / g)

[0169] ・a2-9: "Taftec (registered trademark) M1943" (manufactured by Asahi Kasei Corporation, maleic anhydride-modified SEBS, acid value: 10.0 mgKOH / g)

[0170] (TPU(b))

[0171] ・TPU-1: "Estane (registered trademark) 2103-90AE" (manufactured by Lubrizol, thermoplastic polyurethane)

[0172] (Higher fatty acid metal salt (a3))

[0173] ・StMg: Magnesium stearate manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0174] <Evaluation method>

[0175] (1) Swelling degree

[0176] For the resin composition constituting the A layer or B layer obtained in the embodiments and comparative examples, a 20 mm extruder "D2020" (D (mm) = 20, L / D = 20, compression ratio = 2.0, screw: full spiral) manufactured by Toyo Seiki Seisaku-sho, Ltd. is used to form a single-layer film under the following conditions to obtain a single-layer film.

[0177] Extrusion temperature: resin feed port / barrel inlet / connector / mold

[0178] =180 / 200 / 200 / 200℃

[0179] Screw speed: 40rpm

[0180] Spray volume: 1.3kg / hr

[0181] Pulling roller temperature: 80℃

[0182] Pulling roller speed: 1.1m / min.

[0183] Film thickness: 60μm

[0184] The obtained film was cut into 10 cm × 24 cm, and the mass (W0) was measured. After the cut film was immersed in 1-propanol / water = 60 / 40 (mass ratio) heated to 40°C for 30 minutes, the solvent on the surface of the film was wiped off with a paper towel, and the mass (W1) was measured. The swelling degree (S) was calculated by the following formula.

[0185] S[mass %]={(W1-W0) / W0}×100.

[0186] (2) Solvent resistance (resistance to interlayer delamination after immersion in organic solvents)

[0187] The interlayer delamination resistance of the multilayer structures obtained in the examples and comparative examples was evaluated as follows. The obtained multilayer structure was cut into 3 cm × 3 cm, and the cut film was immersed in 1-propanol / water = 60 / 40 (mass ratio) heated to 40°C for 30 minutes, and the solvent on the surface of the film was wiped off with a paper towel, and the film was naturally cooled for 2 hours. Confirm whether there is interlayer delamination from the end of the film to the center of the film. If there is interlayer delamination, measure the length of the interlayer delamination, and evaluate the interlayer delamination resistance based on the following evaluation criteria.

[0188] Judgment: Benchmark

[0189] A: No interlayer peeling

[0190] B: less than 1mm

[0191] C: 1mm or more and less than 5mm

[0192] D: 5mm or more.

[0193] (3) Interlayer adhesion between layer A and layer B

[0194] The interlayer adhesion between layer A and layer B of the multilayer structure is measured as follows. The obtained multilayer structure is stored in an atmosphere of 23°C and 50% RH, and a short strip of 15 mm is made on the next day of manufacture as a measurement sample. Using the measurement sample, the T-peel strength is measured at a tensile speed of 250 mm / min using an Autograph "AGS-H" manufactured by Shimadzu Corporation in an atmosphere of 23°C and 50% RH. The obtained value (unit: g / 15mm) is used as the interlayer adhesion between layer A and layer B. According to the strength of the interlayer adhesion, the interlayer adhesion is evaluated based on the following evaluation criteria.

[0195] Judgment: Benchmark

[0196] A: 500g / 15mm or more

[0197] B: 400g / 15mm or more and less than 500g / 15mm

[0198] C: 300g / 15mm or more and less than 400g / 15mm

[0199] D: less than 300g / 15mm.

[0200] (4) Appearance

[0201] The appearance of the multilayered structures obtained in Examples and Comparative Examples was evaluated by visual inspection based on the following evaluation criteria.

[0202] Judgment: Benchmark

[0203] A: No lines or stripes, good appearance

[0204] B: Lines are slightly observed relative to the flow direction of the film

[0205] C: Lines are observed relative to the flow direction of the membrane

[0206] D: Lines and streaks are observed relative to the flow direction of the film.

[0207] (5) Dispersibility (determination of dispersed particle size)

[0208] The multilayer structures obtained in the examples and comparative examples were cut with a microtome to expose the cross section. The cross section was observed using a scanning electron microscope (SEM) to measure the dispersed particle size of the thermoplastic resin in the A layer. The SEM observation was performed using SU8010 manufactured by Hitachi High-Tech Nologis Co., Ltd. and a reflected electron detector. It should be noted that the dispersed particle size was set to the average value of the measured values ​​of 10 randomly selected points.

[0209] Judgment: Benchmark

[0210] A: less than 0.3 μm

[0211] B: 0.3 μm or more and less than 0.4 μm

[0212] C: 0.4 μm or more and less than 0.5 μm.

[0213] (6) Oxygen permeability (OTR0)

[0214] The multilayer structures obtained in the examples and comparative examples were humidified at 20°C and 65%RH for 5 days, and the oxygen permeability was measured using "MOCON OX-TRAN 2 / 20" produced by MOCON under the conditions of 20°C and 65%RH according to the method described in JIS K 7126-2 (isobaric method; 2006), and the average value (unit: mL / (m 2 ・day・atm)). The oxygen permeability before the bending test described later is defined as OTR0. It should be noted that if the oxygen permeability is 20mL / (m2 ・day・atm) or less, then under 1 atmosphere pressure, it becomes 1m 2 Furthermore, the oxygen permeability was less than 20 mL within 1 day, so it was judged that it had gas barrier properties.

[0215] Judgment: Benchmark

[0216] A: 5.0mL / m 2 ・day・atm≥OTR0

[0217] B: 5.0mL / m 2 ・day・atm <OTR0≤10.0mL / m 2 ・day・atm

[0218] C: 10.0mL / m 2 ・day・atm <OTR0≤20.0mL / m 2 ・day・atm

[0219] D: 20mL / m 2 ・day・atm <OTR0。

[0220] (7) Bending resistance (gas barrier properties before and after bending (OTR0 / OTR50))

[0221] The multilayer structures obtained in Examples and Comparative Examples were bent repeatedly 50 times in an environment of 23° C. using a “BE1006 Gelber-Francis tester with a constant temperature chamber” manufactured by Tester Industries, Ltd. in accordance with ASTM-F392-74. The gas barrier properties before and after bending were evaluated.

[0222] The oxygen permeability before bending was defined as OTR0, and the oxygen permeability after bending was defined as OTR50, and OTR0 / OTR50 was evaluated based on the following criteria.

[0223] Judgment: Benchmark

[0224] A: OTR0 / OTR50≥0.9

[0225] B: 0.9>OTR0 / OTR50≥0.8

[0226] C: 0.8>OTR0 / OTR50≥0.7

[0227] D:0.7>OTR0 / OTR50.

[0228] (8) Recycling test (torque behavior)

[0229] 60 g of the multilayer structure obtained in the examples and comparative examples was cut (about 1 cm×1 cm) in a manner that conforms to the inlet of the Labtoplast Mill ("20R200" biaxial anisotropic manufactured by Toyo Seiki Seisaku-sho), kneaded at 60 rpm and 200° C., and the torque 5 minutes after the start of kneading was set as T5, and the torque 60 minutes after the start of kneading was set as T60. T60 / T5 was evaluated based on the following criteria. The smaller T60 / T5 is, the less the viscosity change is, the better the long-term running performance is, and the easier it is to reuse.

[0230] Judgment: Benchmark

[0231] A: 1.1 ≥ T60 / T5

[0232] B: 1.5 ≥ T60 / T5> 1.1

[0233] C: 2.0 ≥ T60 / T5> 1.5

[0234] D: T60 / T5>2.0.

[0235] <Example 1>

[0236] 90 parts by mass of Eval (registered trademark) E105B (EVOH-1) and 10 parts by mass of Scona TPPP2112GA (a2-1) were dry-blended and melt-granulated using a twin-screw extruder (diameter 25 mm, L / D = 25) manufactured by Toyo Seiki Seisaku-sho, Ltd., under the conditions of a screw speed of 100 rpm and a discharge of 6.5 kg / hr to prepare an EVOH composition. The obtained EVOH composition and Estane 2103-90AE (TPU-1) were used as materials and supplied to a co-extruder having a 19-layer feed block in a molten state at 190° C. and co-extruded to prepare a multilayer structure having a total of 19 layers in which 9 EVOH layers (A layers) and 10 TPU layers (B layers) were alternately laminated.

[0237] The obtained multilayer structure was observed in cross section using "DIGITAL MICROSCOPE VK-X200" manufactured by KEYENCE. As a result, the average thickness of each layer of layer A (gas barrier layer) was 1.1 μm, and the average thickness of each layer of layer B (TPU layer) was 3.3 μm. It should be noted that each thickness is the average value of the measured values ​​at 10 randomly selected points.

[0238] The obtained multilayer structure was evaluated according to the above (1) to (8). The evaluation results are shown in Table 1. It should be noted that in the obtained multilayer structure, the interlayer adhesion was 730 g / 15 mm, the dispersed particle size of the thermoplastic resin (a2) was 0.23 μm, and the OTR0 was 3.0 mL / (m2 ・day・atm), OTR50 is 3.2mL / (m 2 ・day・atm), OTR0 / OTR50 was 0.94, T5 in the recycling test was 6.72N・m, T60 was 6.82N・m, and T60 / T5 was 1.0.

[0239] In addition, the multilayer structure obtained in Example 1 was embedded with epoxy resin and transverse sections were prepared using a microtome. The obtained transverse sections were gas-stained with solid osmium oxide for 5 days and observed using a transmission electron microscope (TEM) "JEM2100" manufactured by JEOL Ltd. at a magnification of 5000. The TEM image of the cross section of the observed A layer is shown in FIG. Figure 1 It was confirmed that EVOH (a1) was dyed gray or black and was dispersed in the dispersed particles of the thermoplastic resin (a2) in a scattered pattern. The dispersed particle size of EVOH (a1) in the dispersed particles of the thermoplastic resin (a2) was 0.05 μm as the average value of the measured values ​​of 10 randomly selected points.

[0240] <Examples 2 to 30, Comparative Examples 1 to 4>

[0241] The evaluation was carried out using the multilayer structure in the same manner as in Example 1 except that the changes were made as described in Tables 1 to 3. The evaluation results are shown in Tables 1 to 3. Tables 1 to 3 also show the MFR (melt flow rate) of each thermoplastic resin (a2) used.

[0242]

[0243]

[0244]

[0245] As shown in Tables 1 to 3, Examples 1 to 30 have good solvent resistance (interlayer delamination resistance after immersion in an organic solvent), gas barrier properties, and bending resistance. It can be seen that Examples 1 to 30 also have good interlayer adhesion, appearance, dispersibility, and recyclability. In addition, when Examples 7 to 9, which are the same except for the presence or absence of metal salt, are compared, it can be seen that by adding a metal salt to the A layer, the interlayer adhesion and recyclability are improved.

[0246] On the other hand, Comparative Example 1 in which the A layer does not contain the thermoplastic resin (a2) has poor solvent resistance, and Comparative Example 2 in which the content of the thermoplastic resin (a2) in the A layer is too high has poor gas barrier properties, interlayer adhesion, and recyclability. In addition, in Comparative Example 3 in which the total number of layers of the A layer and the B layer is small, the solvent resistance is sufficient but the bending resistance is poor. In addition, when Comparative Example 1 (19 layers) and Comparative Example 4 (3 layers) are compared, the solvent resistance of Comparative Example 1 is D, while the solvent resistance of Comparative Example 4 is C. That is, it can be seen that interlayer delamination after immersion in an organic solvent is a phenomenon that occurs significantly when the number of layers is large.

[0247] <Example 31>

[0248] A laminate was prepared in the same manner as in Example 1 except that the average thickness of the layer corresponding to the polyurethane layer (B1) was adjusted to 3.3 μm and the average thickness of the layer corresponding to the polyurethane layer (B2) was adjusted to 20 μm. The interlayer adhesion of the obtained laminate was 750 g / 15 mm, the dispersed particle size of the thermoplastic resin (a2) in the A layer was 0.23 μm, and the OTR0 was 3.0 mL / (m 2 ・day・atm), OTR50 is 3.1mL / (m 2 ・day・atm), OTR0 / OTR50 was 0.97, T5 in the recycling test was 10.51N・m, T60 was 10.75N・m, and T60 / T5 was 1.02. In addition, the solvent resistance, appearance, and dispersibility were evaluated in the same manner as in Example 1, and all were judged to be A.

[0249] <Example 32>

[0250] As a protective layer (D) directly laminated on the outside of the polyurethane layer (B2) of Example 31, a resin composition of TPU-1:EVOH composition prepared in Example 1 = 95:5 was used, and two layers of protective layers (D) were set by coextrusion to prepare a laminate with a total number of 21 layers. Except for this, a laminate was prepared in the same manner as in Example 31 and evaluated. The average thickness of each layer of the protective layer (D) was 500 μm. The interlayer adhesion of the obtained laminate was 780 g / 15 mm, the dispersed particle size of the thermoplastic resin (a2) in the A layer was 0.25 μm, and the OTR0 was 3.0 mL / (m 2 ・day・atm), OTR50 is 3.1mL / (m 2 ・day・atm), OTR0 / OTR50 was 0.97, T5 in the recycling test was 18.75N・m, T60 was 18.21N・m, and T60 / T5 was 0.97. In addition, the solvent resistance, appearance, and dispersibility were evaluated in the same manner as in Example 1, and all were judged to be A.

[0251] Industrial Applicability

[0252] The multilayer structure of the present invention can be used as a material requiring gas barrier properties, durability, stretchability, etc., such as food packaging materials, medical container packaging materials, other container packaging materials, industrial sheets, building material sheets, agricultural sheets, geological treatment films, radon barrier films, other sheets, other various pipes, etc. In particular, the multilayer structure of the present invention can be suitably used as a material such as a gas barrier film laminated on a film-like rubber product such as a tire inner liner, a shoe sole air cushioning material, an accumulator inner bag, an inflatable ball, and an air spring.

Claims

1. A multilayer structure comprising a gas barrier layer A and a polyurethane layer B, wherein the gas barrier layer A comprises an ethylene-vinyl alcohol copolymer a1 and a thermoplastic resin a2 having a functional group capable of reacting with the ethylene-vinyl alcohol copolymer a1, and the polyurethane layer B comprises a thermoplastic polyurethane b, The content of the thermoplastic resin a2 is 0.1 to 30 parts by mass relative to 100 parts by mass of the total of the ethylene-vinyl alcohol copolymer a1 and the thermoplastic resin a2, the multilayer structure comprises a structure in which at least one set of gas barrier layers A and polyurethane layers B are directly laminated, the total number of gas barrier layers A and polyurethane layers B is 9 or more and 300 or less, the acid value of the thermoplastic resin a2 is 15 to 50 mgKOH / g, The thermoplastic resin a2 is at least one selected from the group consisting of modified polyethylene, modified polypropylene, modified ethylene-vinyl acetate copolymer, and modified ethylene-ethyl acrylate copolymer.

2. The multilayer structure according to claim 1, wherein The functional group possessed by the thermoplastic resin a2 is a carboxyl group or a derivative thereof.

3. The multilayer structure according to claim 1 or 2, wherein The ethylene unit content of the ethylene-vinyl alcohol copolymer a1 is 20 mol% or more and 60 mol% or less.

4. The multilayer structure according to claim 1 or 2, wherein The gas barrier layer A further contains a higher fatty acid metal salt a3.

5. The multilayer structure according to claim 1 or 2, wherein Gas barrier layers A and polyurethane layers B are alternately laminated.

6. The multilayer structure according to claim 5, wherein The polyurethane layer B includes a polyurethane layer B1 on both surfaces of which the gas barrier layer A is directly laminated, and a polyurethane layer B2 on only one surface of which the gas barrier layer A is directly laminated. 7 . The multilayer structure according to claim 6 , comprising a protective layer D directly laminated on the polyurethane layer B2 , wherein the protective layer D comprises a thermoplastic polyurethane x.

8. The multilayer structure according to claim 7, wherein The protective layer D contains ethylene-vinyl alcohol copolymer y.

9. The multilayer structure according to claim 7, wherein The average thickness of each protective layer D is 300 μm or more and 800 μm or less.

10. The multilayer structure according to claim 1 or 2, wherein The average thickness of the gas barrier layer A per layer is 0.1 μm or more and 15 μm or less.

11. The multilayer structure according to claim 1 or 2, wherein The average thickness of the polyurethane layer B per layer is 0.1 μm or more and 30 μm or less.

12. The multilayer structure according to claim 1 or 2, wherein The gas barrier layer A forms a phase-separated structure having a sea phase and an island phase, the sea phase containing the ethylene-vinyl alcohol copolymer a1 and the island phase containing the thermoplastic resin a2.

13. The multilayer structure according to claim 12, wherein A phase containing the ethylene-vinyl alcohol copolymer a1 is further provided inside the island phase. 14 . A molded article comprising the multilayer structure according to claim 1 , wherein at least one of the gas barrier layer A and the polyurethane layer B contains a colorant. 15 . A method for producing a molded article, comprising the step of bringing the multilayer structure according to claim 1 into contact with a treatment liquid containing an organic solvent.

16. The method for producing a molded body according to claim 15, wherein: The treatment liquid contains a colorant.

Citation Information

Patent Citations

  • Modified ethylene-vinyl alcohol copolymer and multilayer structure

    JP2014034647A

  • Multilayer structure and method for producing same

    WO2011068105A1

  • Laminate for inner liner, and tyre using same

    CN104507707A

  • Resin composition, method for producing same and multi-layered structure using same

    CN109642058A

  • Laminated body, its manufacturing method and tire using it

    JP2008024228A